The Ownership Structure and Dividend Payout Policy in Pakistan: Evidence from KSE 100 Index Non-financial Firms - Dr Syed Hassan Raza,Muhammad Zahoor,Muhammad Hafeez (PJE, 2023)
.................................................................................